Utilization of Sugarcane Bagasse Fiber in Composite Board Mixtures as a Sound Absorber - Ihat Solihat; Yusuf Sopian (Jurnal Teknik dan Science, 2025)
An Noise occurring in a room can be reduced or dampened in intensity by installing composite boards on the walls. Composite board material is made from a mixture of resin and sugarcane bagasse fiber. Sugarcane bagasse is a by-product of sugarcane juice extraction, commonly found around sugar factories or as waste from sugarcane juice processing. The utilization of this bagasse as a mixture in composite boards with resin was carried out using board dimensions of 30 × 30 × 1 cm. The composition ratios between bagasse and resin were 60:40, 70:30, 75:25, and 80:20.Based on sound wave testing at frequencies of 250 Hz, 500 Hz, and 750 Hz, the best sound absorption performance was found at the 60:40 composition at a frequency of 750 Hz, where the initial sound intensity was 95.5 dB and was reduced by 62.8 dB. This result indicates a sound absorption coefficient of 0.408, which is relatively good. The lowest absorption was observed at the 80:20 composition with a coefficient of 0.0296 at a low frequency of 250 Hz. This phenomenon occurs because a higher resin content results in a denser structure that reduces sound absorption, whereas a higher fiber content leads to increased porosity, enhancing the composite's ability to absorb sound.